2003
DOI: 10.1136/adc.88.8.695
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors for type 1 diabetes in Rome and province

Abstract: Background: In subjects genetically susceptible to type 1 diabetes, exposure to environmental factors during the gestational period, the neonatal period, and the first years of life is thought to play an important role in triggering the immune process leading to β cell destruction. Aims: To investigate risk factors for inhabitants of continental Italy. Methods: A case-control study of 150 type 1 diabetes cases and 750 control subjects (age range 6-18 years) was carried out in Rome and its province, measuring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 17 publications
3
51
1
1
Order By: Relevance
“…Another study was excluded as it contained fewer than 15 cases [29]. A meeting abstract [31] was replaced with the subsequently published article [43] and, after contact with authors, an earlier report from a cohort [35] was replaced with a later report [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study was excluded as it contained fewer than 15 cases [29]. A meeting abstract [31] was replaced with the subsequently published article [43] and, after contact with authors, an earlier report from a cohort [35] was replaced with a later report [18].…”
Section: Resultsmentioning
confidence: 99%
“…This observed increase in diabetes risk after Caesarean section delivery could not be explained by the confounding influence of birthweight, gestational age, maternal age, birth order, maternal diabetes or breastfeeding. Table 1 b Breast-feeding was categorised as breast-feeding at discharge from hospital [18,32], any breast-feeding [15,25,27], breast-feeding for approximately 3 months or more [30,40,43] and breast-feeding for approximately 4 months or more [37][38][39] Ref. cat., reference category…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this research seem inconsistent, as some studies have concluded that high birthweight is associated with increased diabetes risk [8] or reduced diabetes risk [9], while others have shown no association with type 1 diabetes risk [10]. Interpretation of these findings is made more difficult because studies have reported associations using many different categorisations of birthweight [8,[11][12][13][14], with some [15,16] only reporting findings for the extremes of birthweight and others [17][18][19][20][21] not reporting their birthweight results in any detail, concentrating instead on other findings. This could lead to reporting bias if the decision to report birthweight findings was influenced by whether or not results were interesting or 'statistically significant'.…”
Section: Introductionmentioning
confidence: 94%
“…Adult-onset autoimmune diabetic subjects were selected using the following inclusion criteria: 1) an initial diagnosis of type 2 diabetes according to the American Diabetes Association (14), 2) documented antibody positivity for GADAs (15), 3) no insulin requirement and no evidence of ketosis from diagnosis to screening time, and 4) disease duration between 6 months and 5 years. Type 1 diabetic subjects (n ϭ 558) (age at onset 14.9 Ϯ 7.8 years) were recruited by participating centers of the Immunotherapy Diabetes (IMDIAB) group in the Lazio region of central Italy (16). The control group comprised normoglycemic subjects (n ϭ 545) with no family history of autoimmune disorders (aged 30 Ϯ 5 years), collected from the Blood Transfusion Service of Sapienza University of Rome.…”
mentioning
confidence: 99%